2018
DOI: 10.1182/blood-2017-07-740993
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 expression and clinical PD-1 blockade in B-cell lymphomas

Abstract: Programmed cell death protein 1 (PD-1) blockade targeting the PD-1 immune checkpoint has demonstrated unprecedented clinical efficacy in the treatment of advanced cancers including hematologic malignancies. This article reviews the landscape of PD-1/programmed death-ligand 1 (PD-L1) expression and current PD-1 blockade immunotherapy trials in B-cell lymphomas. Most notably, in relapsed/refractory classical Hodgkin lymphoma, which frequently has increased PD-1 tumor-infiltrating T cells, 9p24.1 genetic alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
318
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(331 citation statements)
references
References 146 publications
(279 reference statements)
10
318
1
2
Order By: Relevance
“…Standardized incidence ratios of splenic marginal zone lymphomas is markedly increased in young adults after solid organ transplantation (Clarke et al, 2013), a clear indication that immune surveillance may prevent emergence of these lymphomas. Consistently, the presence of PD-1 positive exhausted T-cells has been reported in marginal zone lymphomas (Xu-Monette et al, 2017). All indolent lymphomas may evolve towards aggressive transformation with an increased proliferation index and decreased tumor doubling time.…”
Section: Introductionsupporting
confidence: 79%
“…Standardized incidence ratios of splenic marginal zone lymphomas is markedly increased in young adults after solid organ transplantation (Clarke et al, 2013), a clear indication that immune surveillance may prevent emergence of these lymphomas. Consistently, the presence of PD-1 positive exhausted T-cells has been reported in marginal zone lymphomas (Xu-Monette et al, 2017). All indolent lymphomas may evolve towards aggressive transformation with an increased proliferation index and decreased tumor doubling time.…”
Section: Introductionsupporting
confidence: 79%
“…So far there has been very limited testing of anti‐PD‐1 or PD‐L1 therapy in CLL. Interim results presented at conferences have not provided any firm conclusions for efficacy to date (Xu‐Monette et al , ). A trial of anti‐PD‐1 (pembrolizumab) therapy in relapsed and Richter‐transformed patients demonstrated objective clinical responses in the Richter‐transformed patients (4/9) but none in the relapsed CLL patients ( n = 16) (Table ; Ding et al , ).…”
Section: T Cell Abnormalities In Cllmentioning
confidence: 99%
“…Expression of PD-L1 by tumor cells and effect of anti-PD-1 immune therapy has been clearly demonstrated in Hodgkin’s lymphoma, a tumor which is constantly associated with both NF-κB and STAT3 activation. In DLBCL, expression of PD-L1 is variable but participates to the gene immune escape signature of ABC-DLBCLs (3,7). ABC-DLBCL are not only associated with NF-κB activation but may exhibit a chronic active BCR (13) and are sensitive to BTK inhibitors (14).…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy of immunotherapies against the PD-1/PD-L1 axis in breast or colon cancers demonstrated the importance of the immune checkpoints in the control of emergence and growth of tumors (2). As reviewed recently, various publications have indicated that disruption of immune checkpoints is also a critical step in B-cell non-Hodgkin’s Lymphomas (NHL) (3). NF-κB, one of the most cited transcription factor in B-cell lymphomas, is able to increase tumor cell expression of PD-L1 either directly or indirectly (3).…”
Section: Introductionmentioning
confidence: 99%